Legal protection of intellectual property rights in the context of economic globalization: A case study of copyright enforcement in international markets - Rahman, Hanfi Pauzia; Permana, Natasya Amanda Eka; Nissa, Vinka Khoerun; Kartina, Ratu Mawar; Andri, Gusti Yosi (Indonesian Journal of Multidisciplinary Science, 2024)
Intellectual property rights are an important part of intellectual property rights that have a very wide scope of objects. In the era of economic globalization, intellectual property is becoming increasingly important as competition between companies and individuals around the world intensifies. However, there are also challenges that arise in the form of violations of Intellectual Property Rights that pose a serious threat to rights holders. Therefore, the purpose of this study is to determine the legal protection of intellectual Property Rights in the context of economic internationalization. The data collection technique used is a literature study, where relevant data is collected from various related literature sources. Finally, conclusions are drawn to identify important findings from the data analysis that has been carried out. This study can help strengthen theoretical foundations about the role of law in protecting innovation, artwork, and intellectual creation in an ever-changing global economy. This research can also open the door for further research to understand how legal regulation can accommodate rapid and complex global economic developments, as well as foster innovation and inclusive economic sustainability.